The Role of Corporate Governance as a Moderating Variable in Relationship of Determinant Factors Stock Return - Dian Rokhmawati; Desman Serius Nazara; Sutrisno; Muhammad Irvan; Deddy Novie Citra Arta (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The objective of this study is to examine the role of corporate governance as moderating variable in relationship between all of independent variables toward stock return. The type of research used in this research is causal associative research. Casual associative research is research that aims to determine the effect or relationship between two or more variables. This research is also a quantitative study. The quantitative method is a scientific approach that views a reality as classifiable, concrete, observable and measurable, the variable relationship is causal in nature where the research data is in the form of numbers and the analysis uses statistics. The conclusion from this study is that the Liquidity Variable has no effect on Stock Returns. Profitability Variable influences Stock Return. Solvency variable has no effect on Stock Return. Accounting Profit Variable influences Stock Return. Operating Cash Flow Variable influences Stock Return. The Independent Commissioner variable cannot moderate the influence of Liquidity on Stock Returns. Independent Commissioners cannot moderate the influence of Profitability on Stock Returns. Independent Commissioners cannot moderate the influence of Solvency on Stock Returns. Independent Commissioners cannot moderate the influence of Accounting Profits on Stock Returns. Independent Commissioners cannot moderate the influence of Operating Cash Flow on Stock Returns. The Audit Committee cannot moderate the influence of Liquidity, Profitability, Solvency, Accounting Profit and Operating Cash Flow on Stock Returns.